Micro Plastic Part Filling Capabilities through Simulation and Experiment A Case Study on Micro Gear Shape - M., Azuddin; Zahari, Taha (Elsevier, 2016)
Injection molding is one of widely used plastic processing techniques for the plastic products manufacture. It is well suited for mass production because the raw material conversion into a final product usually requires only a single operation. Moreover, minor or no finishing process is required. The process is capable of producing very complicated part geometries with light specifications, Due to high productivity and flexibility, injection molding applications have grown rapidly in various industries